Understanding the Moryones of the Moriones Lenten Rites: A Phenomenological Inquiry - Asiones, Noel; Parado, Ulysses John (Technium Social Sciences Journal, 2022)
Popular religiosity is one of the intriguing phenomena in the Roman Catholic religious tradition and practice. We used descriptive phenomenology to describe popular religiosity from the perspectives and collective experiences of 15 devotees of the Moriones Lenten Rites in Marinduque. Cool and warm analyses conducted on the qualitative data semi-structured interviews yielded three significant themes that describe the shapes and dynamism of the Moryones phenomenon, namely, remembering the past, giving thanks for the present, and embracing one’s fellow others. Through the years, popular expressions of religiosity such as the Moriones Lenten Rites were able to secure a foothold in the private lives of ordinary Filipino Catholics and have continued to flourish despite secularizing and modernizing influences in Philippine society.